(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2017)
Interested in many scholars and reseachers the subject of the media and means varied his roleinfluential in the definition of the public of issues and political, cultural, social and because of its spread wide and ability to address the people of all levels effect them in the formation consciousness of those issues and types of this awareness is an awareness of the tax, contribute to media formation consciousness tax through the definition of people what tax and importance of the role of its revenues to supplement the state budget by posting tax laws and regulations of applied and all what respect process account tax, to be in charge of the tax familiar enough about this, which avoid being cheated taxmisleading when reviewing the Chambers tax.So the tax awareness has abig role in increasing tax revenue and in get a good awareness of tax the taxpayer has to be agood media of various types .